Visualising the Emigrant Letter - Moreton, Emma (Université de Poitiers, 2014)
Emigrant letters are a rich resource for teaching and learning, transcending disciplinary and methodological boundaries. They are expressive and indicative of correspondents’ identities, values, preoccupations and beliefs, providing a powerful source of information about migration issues and shedding light on processes of language change and variation. Although many emigrant letter collections have now been digitised, not all are properly archived; some are reduplicated and others are in danger of being lost. The documentation and preservation of such letters is, therefore, a particularly pressing need. In 2013, an AHRC research network was established to look at ways of improving interconnectivity between digital collections of migrant correspondence. This paper reports on work carried out so far, focusing on how emigrant letter projects might move beyond the digitisation stage to exploit text content and enhance usability and searchability through the use of visualisation tools.